Penerapan Metode Role Playing pada Pembelajaran Pendidikan Pancasila dan Kewarganegaraan dalam Upaya Pembentukan Civic Disposition Siswa Kelas X SMK Negeri 7 Bone: Penelitian - Armawati; Andi Tabrani Rasyid; Maming Genda; Andi Tenri Sua (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to analyze the application of the role playing method in Pancasila and citizenship education learning to form civic disposition in class X students of SMK Negeri 7 Bone. This study uses a qualitative research method with observation, interview and documentation data collection techniques. Data analysis techniques are data reduction, data presentation and conclusions. The results of the study indicate that the role playing method is effective in forming students' civic disposition because it can increase students' enthusiasm, improve character and develop students' communication skills. They feel that this learning is more interactive and motivated to apply civic disposition values ​​in everyday life.